Incidencia psicológica del vínculo afectivo en adolescentes consumidores de sustancias psicoactivas a partir de un trabajo de revisión documental en países Latinoamericanos durante los años 2010 al 2021 - Ingrid Johana, Fonseca Cruz (Universidad Antonio Nariño, 2022)
Affective bonds are bonds, which unite from the first moments of life towards a father or mother figure, in which the human being seeks security and well-being by being in contact with the other who has given him the care, developing an affective language. On the other hand, the consumption of psychoactive substances can be the result of fractured affective bonds in the family environment and a social environment influential in the transformation of the subject.